ANALISA SISTEM MIXED NAVIGATION ENVIRONMENT TERHADAP BEBAN KERJA AIR TRAFFIC CONTROLLER DI PERUM LPPNPI KANTOR CABANG PEMBANTU LAMPUNG - Moch Difal Syaifudin; Meita Maharani Sukma; Hari Fitrianto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study aims to determine the analysis of the mixed navigation environment system on the ATC workload after the implementation of RNP-1 at Perum LPPNPI Lampung sub-branch office. The research sample used was a saturated sample because the total population was not greater than 10 people, so it was taken from the entire population in the ADC/APP combined service service unit. The object is directed at ATC at the ADC/APP service unit combined with services at Perum LPPNPI, Lampung Sub-Branch Office. The research method used is a qualitative method. In addition, the data collection method used in this study is the method of observation, questionnaires and interviews as a data collection tool at Radin Inten II Airport Lampung. Based on the results of the study, the average Likert scale questionnaire results obtained a value of 90% and it can be concluded that ATC respondents strongly agree that the mixed navigation environment system can increase the workload of the air traffic controller at Perum LPPNPI, Lampung Sub-Branch.